2018
DOI: 10.1387/ijdb.180214jm
|View full text |Cite
|
Sign up to set email alerts
|

HOXA5 protein expression and genetic fate mapping show lineage restriction in the developing musculoskeletal system

Abstract: HOX proteins act during development to regulate musculoskeletal morphology. HOXA5 patterns skeletal structures surrounding the cervical-thoracic transition including the vertebrae, ribs, sternum and forelimb girdle. However, the tissue types in which it acts to pattern the skeleton, and the ultimate fates of embryonic cells that activate Hoxa5 expression are unknown. A detailed characterization of HOXA5 expression by immunofluorescence was combined with Cre/LoxP genetic lineage tracing to map the fate of Hoxa5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…This broad spatial domain suggested that expression of both proteins includes but is not limited to prospective brown adipocytes. In closer view, neither protein is expressed in skeletal muscle (Figures 2E-H; red outline marks the epaxial muscle mass), consistent with our previous reports for HOXA5 (Landry-Truchon et al, 2017;Holzman et al, 2018). However, EBF2 and HOXA5 are co-expressed in muscle connective tissue (MCT) fibroblasts interspersed within the muscle ( Figure 2H, red arrowheads).…”
Section: Hoxa5 Protein Is Expressed In Bat Adipocytes and Fibroblastssupporting
confidence: 90%
See 4 more Smart Citations
“…This broad spatial domain suggested that expression of both proteins includes but is not limited to prospective brown adipocytes. In closer view, neither protein is expressed in skeletal muscle (Figures 2E-H; red outline marks the epaxial muscle mass), consistent with our previous reports for HOXA5 (Landry-Truchon et al, 2017;Holzman et al, 2018). However, EBF2 and HOXA5 are co-expressed in muscle connective tissue (MCT) fibroblasts interspersed within the muscle ( Figure 2H, red arrowheads).…”
Section: Hoxa5 Protein Is Expressed In Bat Adipocytes and Fibroblastssupporting
confidence: 90%
“…Immunostaining was performed following previously described protocols (Holzman et al, 2018;McGlinn et al, 2019). Briefly, embryos were fixed in 4% paraformaldehyde at 4 • C and embedded in OCT.…”
Section: Immunofluorescencementioning
confidence: 99%
See 3 more Smart Citations